Propuesta De Automatización Del Sistema De Drenaje De Los Tanques De Almacenamiento De Crudo (Caso Estación Acacias) (2022)
Process automation in industry plays a key role in improving efficiency, quality, safety and competitiveness, by reducing the dependence on human labor in repetitive and monotonous tasks, automation allows greater productivity and accuracy in the execution of processes, while minimizing human errors; in addition, automation technology offers the ability to operate 24 hours a day, 7 days a week, which boosts continuous production and reduces labor costs. Based on a descriptive study under a mixed research approach, the current process of draining the crude oil tanks of the Acacias Station is analyzed, obtaining the different resources and factors that influence this activity, at the same time, through different case studies associated to the automation of hydrocarbon tanks, the required inputs that allow budgeting the automation are established. Keywords: Automation, drainage system, valves, storage tanks, crude oil